THE INFLUENCE OF CULTURE AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AT PT. BANK MANDIRI (PERSERO), TBK AREA MAKASSAR SAM RATULANGI IN MAKASSAR CITY - surya anggraeni sayitno (Scientia Integritas Utama, 2022)
This study aims to determine the effect of culture and leadership style on job satisfaction and employee performance at PT. Bank Mandiri (Persero), Tbk Area Makassar Sam Ratulangi. The sample in this study were employees with more than 3 (three) years of service using a questionnaire with a total sample of 170 employees. The data were analyzed using a quantitative approach and processed using the SPSS version 22 application. From the results of this study, it was found that there was a positive and significant influence between culture and leadership style on employee performance. This shows that there is a good relationship between employees in implementing the daily work culture and is supported by the close relationship between superiors and subordinates.